2003
DOI: 10.1172/jci16956
|View full text |Cite
|
Sign up to set email alerts
|

Collecting duct–specific gene inactivation of αENaC in the mouse kidney does not impair sodium and potassium balance

Abstract: Aldosterone controls the final sodium reabsorption and potassium secretion in the kidney by regulating the activity of the epithelial sodium channel (ENaC) in the aldosterone-sensitive distal nephron (ASDN). ASDN consists of the last portion of the distal convoluted tubule (late DCT), the connecting tubule (CNT), and the collecting duct (CD) (i.e., the cortical CD [CCD] and the medullary CD [MCD]). It has been proposed that the control of sodium transport in the CCD is essential for achieving sodium and potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(82 citation statements)
references
References 50 publications
8
72
2
Order By: Relevance
“…These authors showed that mice lacking α-ENaC in the CCD maintain their Na + balance, suggesting that most of the ENaC-Na + absorption occurs in the early segments of the collecting duct system, i.e., the late DCT and connecting tubule (CNT) segments. Electrophysiological analyses of primary cultures of isolated DCTs dissected before their branching in the CCD (i.e., CNT) and isolated CCDs fully confirmed the pioneering study of Rubera et al [116]: Primary cultured DCT dissected from α-ENaC-deficient mice exhibited the same high electrical transepithelial resistance (R T ) and potential (P D ), and amiloride-sensitive I sc as DCT dissected from wild-type mice counterparts. In sharp contrast, CCD dissected from the kidneys of α-ENaC-deficient mice developed high R T and very low P D and did not respond to arginine vasopressin (Fig.…”
Section: Primary Cultures Of Renal Tubule Cells Derived From Normal Asupporting
confidence: 62%
See 2 more Smart Citations
“…These authors showed that mice lacking α-ENaC in the CCD maintain their Na + balance, suggesting that most of the ENaC-Na + absorption occurs in the early segments of the collecting duct system, i.e., the late DCT and connecting tubule (CNT) segments. Electrophysiological analyses of primary cultures of isolated DCTs dissected before their branching in the CCD (i.e., CNT) and isolated CCDs fully confirmed the pioneering study of Rubera et al [116]: Primary cultured DCT dissected from α-ENaC-deficient mice exhibited the same high electrical transepithelial resistance (R T ) and potential (P D ), and amiloride-sensitive I sc as DCT dissected from wild-type mice counterparts. In sharp contrast, CCD dissected from the kidneys of α-ENaC-deficient mice developed high R T and very low P D and did not respond to arginine vasopressin (Fig.…”
Section: Primary Cultures Of Renal Tubule Cells Derived From Normal Asupporting
confidence: 62%
“…3 Electrophysiological properties of primary cultures of late distal and early collecting duct cells dissected from kidneys of transgenic mice harboring specific, αENaC-activating gene in the collecting duct. Isolated late DCT (including CNT) microdissected from the kidneys of Scnn 1a loxlox (loxlox) and Scnn 1a loxloxCre (loxloxCre) mice [116] and grown until confluency on collagencoated filters (14 days after seeding) were incubated in hormone-free, serum-free medium. The transepithelial electrical resistance (R T ), potential (P D ), and amiloride-sensitive short-circuit current (AmsI sc ) were then measured on cultured loxlox DCT or CCD and loxloxCre DCT or CCD.…”
Section: Strategies For Obtaining Immortalized Renal Tubule Cell Linementioning
confidence: 99%
See 1 more Smart Citation
“…These nephron segments have not yet been studied in Liddle mice but are thought to contribute substantially to ENaC-mediated sodium absorption in the kidney. [20][21][22] Previously, we reported that ENaC activity in DCT2/CNT is constitutively high and independent of aldosterone. This is in contrast to the aldosterone dependence of ENaC activity in CNT/CCD.…”
mentioning
confidence: 98%
“…Recently, a tissue-specific knockout of the a ENaC subunit in the CCD has been generated in the mouse (Rubera et al 2003). The absence of a ENaC protein in the CCD and OMCD, together with an undetectable ENaC activity in these nephron segments, has surprisingly little effect on Na + homeostasis.…”
Section: Enac In the Kidneymentioning
confidence: 99%